2017
DOI: 10.1038/s41598-017-05954-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CXCL12/CXCR4 signaling on neuropathic pain after chronic compression of dorsal root ganglion

Abstract: Neuropathic pain is a complex, chronic pain state that often accompanies tissue damage, inflammation or injury of the nervous system. However the underlying molecular mechanisms still remain unclear. Here, we showed that CXCL12 and CXCR4 were upregulated in the dorsal root ganglion (DRG) after chronic compression of DRG (CCD), and some CXCR4 immunopositive neurons were also immunopositive for the nociceptive neuronal markers IB4, TRPV1, CGRP, and substance P. The incidence and amplitude of CXCL12-induced Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Using CCD model, we found that the expression level of CXCR4 in compressed DRG dramatically increased revealed by immuno uorescent staining which was in accordance with a recent study [12]. The functional nature of the up-regulated CXCR4 was identi ed by our siRNA knockdown assay in which intraganglionar microinjection with CXCR4 siRNA obviously attenuated CCD-induced multiple pain behaviors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using CCD model, we found that the expression level of CXCR4 in compressed DRG dramatically increased revealed by immuno uorescent staining which was in accordance with a recent study [12]. The functional nature of the up-regulated CXCR4 was identi ed by our siRNA knockdown assay in which intraganglionar microinjection with CXCR4 siRNA obviously attenuated CCD-induced multiple pain behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study has showed that activation of CXCR4 could directly modulate primary neuronal excitability by mediating the up-regulation of Nav1.8 under in ammatory pain state [24]. Interestingly, the CXCR4 expression also signi cantly increased in the compressed DRG from CCD mice [12]. Whether the Nav1.8 and Nav1.9 was the downstream effector target for CCD-induced CXCR4 activation remains unclear.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several GPCRs involved in pro-inflammatory pathways, including CCR1 , CCRL2 , CNR1 , CXCR4 , F2R , CHRM1 [66; 68] were found to increase in abundance in cultured DRGs. GPCRs found to be decreased in culture included DRD5 , HTR5A , HTR6 , and some metabotropic glutamate receptors ( GRM s) like GRM4, GRM5 (which was not detected) and GRM7 , all of which have been shown to be highly neural tissue enriched in humans (based on neural proportion score > 0.9 in Ray et al [47]).…”
Section: Resultsmentioning
confidence: 99%
“…Spinal DRGn are afferent neurons of peripheral nervous system and primary neurons of sensory conduction system. With the increasing research on the nervous system, such as the pain mechanism of diseases [1][2][3], spinal cord injury repair [4,5], electrophysiological research [6][7][8][9], it is necessary to establish a simple and easy-to-obtain primary nerve cell culture scheme.…”
Section: Introductionmentioning
confidence: 99%